2010
DOI: 10.1371/journal.pmed.1000374
|View full text |Cite
|
Sign up to set email alerts
|

Association of Secondhand Smoke Exposure with Pediatric Invasive Bacterial Disease and Bacterial Carriage: A Systematic Review and Meta-analysis

Abstract: Majid Ezzati and colleagues report the findings of a systematic review and meta-analysis that probes the association between environmental exposure to secondhand smoke and the epidemiology of pediatric invasive bacterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 76 publications
4
29
1
1
Order By: Relevance
“…However, in a systematic review of the association between ETS exposure and invasive bacterial disease, this association only occurred with meningococcal disease [50]. Another systematic review on the health effects of passive smoking also reported an increased risk for invasive meningococcal disease, pneumococcal carriage, and LRTI in children [51].…”
Section: Resultsmentioning
confidence: 99%
“…However, in a systematic review of the association between ETS exposure and invasive bacterial disease, this association only occurred with meningococcal disease [50]. Another systematic review on the health effects of passive smoking also reported an increased risk for invasive meningococcal disease, pneumococcal carriage, and LRTI in children [51].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there are multiple reports that secondhand smoke increases the incidence of nasal pneumococcal colonization in children (29)(30)(31), further emphasizing the need for additional mechanistic studies (6). In the current study, we sought to establish a mouse model of nasal pneumococcal colonization and cigarette smoke exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies where a multivariate analysis has been carried out, different confounding factors are included in the models, making it difficult to compare. A recent meta-analysis found that second-hand exposure to tobacco smoke was associated with a significantly increased risk of IMD with an OR of 2.02 (95% CI 1.52 to 2.69) 46. In the three studies specifically addressing pre-school children (≤6 years), the association was stronger, but non-significant (OR=3.04, 95% CI 0.89 to 10.47), most likely due to inadequate power even with the combined analysis.…”
Section: Discussionmentioning
confidence: 99%